Understanding natural behavior to improve dairy goat (Capra hircus) management systems. Issue 1 (31st December 2018) - Zobel, Gosia; Neave, Heather W; Webster, Jim
Abstract: Public interest is stimulating farming industries to improve animal welfare in production systems. Indoor housing of ruminants has received scrutiny because of perceived intensiveness and lack of naturalness. Animal welfare has traditionally focused on health benefits (e.g., bedding management and reducing disease) and reducing negative experiences (e.g., painful husbandry practices). Recent attention to animals having "a life worth living" extends expectations to provide increased care and opportunities for positive experiences and natural behaviors. Although not all natural behaviors necessarily contribute to improved welfare, we present evidence for why many are important, and for how they can be promoted in commercial systems. Worldwide, commercial dairy goats ( Capra hircus ) are frequently housed in large open barns with space to move and soft bedding for lying; however, this is not sufficient to promote the range of natural behaviors of goats, which in turn suggests that commercial housing could be improved. The basis for this thinking is from the range of behaviors expressed by the Capra genus. Collectively, these species have evolved cognitive and behavioral strategies to cope with harsh and changing environments, as well as variable and limited vegetation. The rocky and often steep terrain that goats inhabit allows for predator avoidance and access to shelter, so it is not surprising that domesticated goats also seek out elevation and hiding spaces; indeed, their hoof structure is designed for the movement and grip in such rugged environments. The browsing techniques and flexibility in diet selection of wild, feral and extensively managed goats, appears to be equally important to housed goats, highlighting the need for more complexity in how and what goats are fed. Goats naturally live in small, dynamic groups, governed by complex social structures in which horns play a strong role. Commercial housing systems should consider the benefits of more natural-sized social groups and revisit the rationale behind horn removal. We suggest that cognitive stimulation is a potential welfare improvement for goats in commercial settings. Goat cognitive abilities, which enabled success in complex and variable social and physical environments, are unchallenged in uniform environments, potentially leading to negative affective states. We make suggestions for housing improvements that could be readily adopted into current systems without compromising production efficiency.